Caucasian and African American racial disparity in neonatal hospital mortality - Burdjalov, Maria; Qattea, Ibrahim; Nandakumar, Vanishree; Mohamed, Mohamed A.; Aly, Hany (Frontiers in Pediatrics, 2024)
Objective: To examine disparity in hospital mortality among Caucasian (C) and African American (AA) neonates born at different gestational ages (GA). Methods: De-identified national inpatient data were obtained from the Healthcare Cost and Utilization Project (HCUP) from the Agency for Healthcare Research and Quality (AHRQ) for the years 2011-2018. We compared the odds ratio for mortality among C and AA infants by sex and GA category. Analyses were repeated after controlling for multiple maternal and neonatal confounding variables in a logistic regression model. Results: The study included 18,758,233 infants; 78.3% of them were C and 21.7% were AA. Compared to C population, AA population has a significantly higher mortality in term infants born at GA ≥ 36 weeks. The racial/ethnic disparity in preterm infants was inconsistent without any difference at 35-36 weeks in male and female infants. The overall aOR for mortality in AA in all male preterm infants ≤ 36 weeks was 1.44 (1.39-1.49), <0.01; and the overall aOR for mortality in AA in all preterm female infants ≤ 36 weeks was 1.38 (1.33-1.44). Conclusion: Racial/Ethnic disparity in hospital mortality exists with higher AA mortality in infants born with GA >36 weeks and less AA mortality in infants born with GA 24-26 weeks.